THE NATURAL AND COMMERCIAL SOURCES OF HYDROXYAPATITE/COLLAGEN COMPOSITES FOR BIOMEDICAL APPLICATIONS: A REVIEW STUDY - MUDHAFAR, MUSTAFA; ALSAILAWI, H. A.; ZAINOL, ISMAIL; SACHIT HAMZAH, MOHAMMED; DHAHI, SAHI JAWAD; MOHAMMED, RUAA KADHIM (International Journal of Applied Pharmaceutics, 2022)
Bone is considered the core unit that forms the human body’s skeleton, consisting primarily of hydroxyapatite (HA) and collagen (Col). The composites of hydroxyapatite/collagen had been prepared through different fabricated techniques and were used in many bone defects as biomaterials for bone tissue engineering. The incorporation of HA and collagen is possible due to the biocompatibility of collagen and the high mechanical properties of the HA. HA/Col composites have been used in many medical and biological fields. Current study have been discussed the synthesis and characterization techniques of HA/Col composites; the study have been included to study the cytotoxicity and cell attachment of the composites, along with their applications, as well as barriers that still remain to their successful development for clinical application.